Yeast opsonization in newborn infants and its relationship to parental atopy. - Richardson, V F (1982)
Sera from 30 of 303 (9.9%) unselected term newborn infants were deficient in their ability to opsonize heat-killed baker's yeasts, an incidence which is almost double that seen in adults. Genetic influence is important in some since the mothers of 10 infants with defective opsonization showed the same defect, but it was not related to the sex or race of the infant or to the atopic state of the parents. In others the defect could be due to a functional maturation delay of the complement system, but not to inhibitory factors in neonatal serum since correction of opsonization was achieved with subopsonizing amounts of normal sera. Significantly more infants had sera with high opsonizing capacity (greater than 80% yeasts phagocytosed) when compared with adults; perhaps antibody independent immune mechanisms like this are important in the newborn. This study shows that a common specific immunodeficiency which may predispose to severe infection or atopy can be identified at birth.